Influence of Pd‐Doping on The Efficiency of In2O3/ZrO2 Catalysts Used for Hydrogenating Dimethyl Oxalate to Ethanol. Issue 4 (24th January 2022) - Xue, Haodong; Qin, Siqian; Wang, Xue; Zhang, Chuancai; Wang, Denghao; Dai, Bin
Abstract: A co‐precipitation method followed by an impregnation method was used to synthesize the x Pd‐In2 O3 /ZrO2 catalysts that could be used for the hydrogenation of dimethyl oxalate to ethanol. The results indicated that x Pd‐In2 O3 /ZrO2 exhibited excellent catalytic activity during the hydrogenation of dimethyl oxalate to ethanol. It was found that Pd−doping could improve the performance of the catalysts. 100 % conversion and 84 % ethanol selectivity could be achieved using the 0.5 % Pd‐In2 O3 /ZrO2 catalyst. In‐depth charact‐erization of the x Pd‐In2 O3 /ZrO2 catalyst revealed the occurrence of hydrogen spillover and the formation of oxygen vacancies on the surface of the catalyst. The improvement in the catalytic activity can be attributed to the increase of activated hydrogen concentration during the process of hydrogen spillover in the presence of Pd and the enhancement of activation capacity (toward dimethyl oxalate) of the catalyst caused by the formation of oxygen vacancies. Abstract : Pd‐In2 O3 /ZrO2 catalytic system was designed and constructed for efficient hydrogenation of dimethyl oxalate to ethanol. The doping of Pd in the system is conducive to the activation of hydrogen and the formation of oxygen vacancy after catalyst reduction. Moreover, the H‐spillover produced by Pd can transfer the activated hydrogen to the active site adsorbed with dimethyl oxalate molecule for effective hydrogenation of dimethyl oxalate. The synergistic effect of Pd and In2Ox promoted the deep hydrogenation of dimethyl oxalate to ethanol.